Meta-analysis of microsomal epoxide hydrolase gene polymorphism and risk of hepatocellular carcinoma. - Jian-Hong Zhong (Public Library of Science (PLoS), 2013)
Background Hepatocarcinogenesis is a complex process that may be influenced by many factors, including polymorphism in microsomal epoxide hydrolase (mEH). Previous work suggests an association between the Tyr113His and His139Arg mEH polymorphisms and susceptibility to hepatocellular carcinoma (HCC), but the results have been inconsistent. Methods PubMed, EMBASE, Google Scholar and the Chinese National Knowledge Infrastructure databases were systematically searched to identify relevant studies. A meta-analysis was performed to examine the association between Tyr113His and His139Arg mEH polymorphism and susceptibility to HCC. Odds ratios (ORs) and 95% confidence intervals (95% CIs) were calculated. Results Eleven studies were included in the meta-analysis, involving 1,696 HCC cases and 3,600 controls. The 113His- mEH allele was significantly associated with increased risk of HCC based on allelic contrast (OR = 1.35, 95% CI = 1.04-1.75, p = 0.02), homozygote comparison (OR = 1.65, 95% CI = 1.07-2.54, p = 0.02) and a recessive genetic model (OR = 1.54, 95% CI = 1.21-1.96, p<0.001), while individuals carrying the Arg139Arg mEH genotype had no association with increased or decreased risk of HCC. Conclusion The 113His- allele polymorphism in mEH may be a risk factor for hepatocarcinogenesis, while the mEH 139Arg- allele may not be a risk or protective factor. There is substantial evidence that mEH polymorphisms interact synergistically with other genes and the environment to modulate risk of HCC. Further large and well-designed studies are needed to confirm these conclusions.